The Relationships Between Instagram Social Media Usage, Hedonic Shopping Motives and Financial Literacy on Impulse Buying - Triwidisari, Asri; Nurkhin, Ahmad; Muhsin, Muhsin (Fakultas Ekonomi, Universitas Negeri Semarang, 2017)
This research aims to determine the effect of using instagram social media and hedonic shopping motives to impulse buying media and to know whether financial literacy is able to moderate the influence of instagram social media use and hedonic shopping motives to impulse buying. This type of research is quantitative research. The population of this research was students of Accounting Economics Education Study Program of Economics Faculty of Universitas Negeri Semarang (UNNES). The research sample was 110 students of class of 2013 which chosen by using purposive sampling technique. The data was analyzed by using descriptive statistic, simple regression analysis, and interaction test (moderation). The result of the research shows that instagram social media usage and hedonic shopping motives have positive and significant effect to students’ impulse buying. The result of regression analysis shows that financial literacy has negative and significant effect on impulse buying. Thus, financial literacy can moderate the influence of instagram social media usage to impulse buying. However, the other regressive result indicates that financial literacy is not able to moderate the influence of hedonic shopping motives on impulse buying.